Longshot - Francis, Dick (G.P. Putnam's Sons New York, 1990)
Writer John Kendall whose books run from travel guides to manuals on safety in the jungle and desert is in the hungry interval between the acceptance and the publication of his first novel. He agree to write the biography of a race horse trainer, living in the trainer's home while researching his life and his work. But the perils described in his survival guides pale next to the dangers in rural England.
62870
Keywords: Horse racing - trainers. -- Writers -- Mysteries -- England